On multiple solitons of glycolysis reaction-diffusion system for the chemical concentration - Iqbal, Muhammad S.; Baber, Muhammad Z.; İnç, Mustafa; Younis, Muhammad; Ahmed, Nauman; Qasim, Muhammad (World Scientific Publ Co Pte Ltd, 2024)
In this research, the nonlinear mathematical model for enzyme-catalyzed reaction-diffusion phenomena has been analyzed for the exact solutions investigated analytically. As a result, it is critical to investigate this concept from a mathematical standpoint. The f6-model expansion method is used to extract the analytical solutions which give the chemical concentration. These variables behave differently depending on the diffusion and dimensionless input flux rate parameter. Furthermore, the existence of these solutions is also discussed under different constraint conditions and variables of chemical concentrations are represented in hyperbolic, trigonometric and rational forms. For various values, the 3D behavior of these concentrations is also depicted.
Keywords: Analytical solutions; chemical reaction model; glycolysis system; 06-model expansion method